Software Radio Sampling Rate Selection, Design and Synchronization - Venosa, Elettra; harris, fredric j.; Palmieri, Francesco A. N. (Analog Circuits and Signal Processing, 2012)
Software Radio represents the future of communication devices. By moving a radio's hardware functionalities into software, SWR promises to change the communication devices creating radios that, built on DSP based hardware platforms, are multiservice, multiband, reconfigurable and reprogrammable. This book describes the design of Software Radio (SWR). Rather than providing an overview of digital signal processing and communications, this book focuses on topics which are crucial in the design and development of a SWR, explaining them in a very simple, yet precise manner, giving simulation results that confirm the effectiveness of the proposed design.  Readers will gain in-depth knowledge of key issues so they can actually implement a SWR.  Specifically the book addresses the following issues: proper low-sampling rate selection in the multi-band received signal scenario, architecture design for both software radio receiver and transmitter devices and radio synchronization. Addresses very precisely the most important issues connected to software radio design and implementation; Describes even the most complicated issues in simple terms, making solutions accessible; Uses simulation results to illustrate and prove theoretical concepts; Maximizes use of diagrams to aid in understanding.        .